Exploring equity in global health collaborations: a qualitative study of donor and recipient power dynamics in Liberia - Bernice Dahn; Kristina Talbert-Slagle; Joseph Lewis; Brigid E Cakouros; Johannah Gum; Defne L Levine; Antoinette H Wright (BMJ Global Health)
IntroductionGlobal health collaborations between individuals from high-resource and low-resource settings are complex and often built on hierarchical structures and power differentials that are difficult to change. There have been many calls and frameworks developed to facilitate more equity within these collaborations, yet little is known about the lived experiences of global health donors and recipients working within such collaborations and how those experiences can facilitate more equitable collaboration. Liberia, a postconflict, post-Ebola country, provides an ideal setting to study lived experiences of global health collaborations.MethodsOur qualitative analysis used key informant interviews representing the perspectives of those working on behalf of the Liberian government, Liberian academics, foreign donors and non-governmental organisations and implementing partners. Thematic analysis guided this analysis to explore topics such as financial control, accountability and decision making.ResultsThe first phase of the analysis mapped the existing patterns of priority setting. Priority-setting power was most strongly held by those with financial control (donors), and implementation plans tended to be built on metrics that aim to meet donor expectations. The second phase of the analysis explored the interplay between underlying factors that we identified in our data associated with driving collaborative inequity: history of prior of engagement, level of transparency and patterns of accountability.ConclusionsOur findings highlight that global health collaborations in Liberia are structured to hinder equitable partnerships. The power structure tied to financial ownership offers little space for recipients to have an equitable role in collaborations, which maintains dependence on external aid and ensures that weak systems remain weak. While our study is limited to Liberia, we anticipate that these dynamics are common elsewhere and reinforce the importance of intentional efforts to ensure equitable decision making and power structures in similar settings worldwide.